Faktor-faktor yang Berpengaruh terhadap Perkembangan Pasar Swalayan di Kota Lhokseumawe - Zulkarnaen, Teuku (Jurnal Aplikasi Manajemen, 2008)
This research to know factors what having an effect on and factor what dominant have an effect on to growth of market selfservice in town of Lhokseumawe and to know how big growth of market selfservice in town of Lhokseumawe. Data the taken is primary data and data of skunder. got data primary data through spreading of kuestioner to 58 responder which managing the the market selfservice. While data of skunder is taken away from by data various source of related to this research object. result of from this research indicate that correlation coefficient (R) equal to 0.844 or 84,4% meaning independent varibel can explain variable dependent or equally market location factor, equipment of goods, service, earnings and price have strong relation with growth of market selfservice. Coefficient of Determinasi (R2) equal to 0.713 or 71,3% this have a meaning of that variable dependent can influence by variable of idependent equal to 71,3% and the rest equal to 28.7% will influence by other variable which do not check by this research dapal. medium coefficient of regresi by successively is equal to 0.242(X1), 0.252 ( X2), 0.004 (X3), 0.032 (X4), 0.818 (This X5) have a meaning of where each; every increase 1% each variable of independent hence will follow with change of market selfservice equal to variable value of independent the but this matter of akanterjadi if assumed by other variable in assuming remain to constant.